Temporal variations of cryoconite holes and cryoconite coverage on the ablation ice surface of Qaanaaq Glacier in northwest Greenland - Nozomu Takeuchi; Ryutaro Sakaki; Jun Uetake; Naoko Nagatsuka; Rigen Shimada; Masashi Niwano; Teruo Aoki (Annals of Glaciology, 2018)
Cryoconite holes are water-filled cylindrical holes formed on ablation ice surfaces and commonly observed on glaciers worldwide. Temporal changes of cryoconite holes characteristically <5 cm in diameter were monitored with a time-lapse interval camera over 15 d during the melting season on Qaanaaq Glacier in northwest Greenland. The holes drastically changed their dimensions and synchronously collapsed twice during the study period. When the holes collapsed, the coverage of cryoconite on the ice surface increased from 1.0 to 3.5% in the field of view of the camera, and then decreased again to 0.4% after the holes reformed. Comparison with meteorological data showed that the collapses occurred in cloudy and rainy or windy weather conditions, corresponding to low shortwave solar radiation (68–126 W m−2, 40–55% of the incoming flux). In contrast, holes developed in sunny conditions correspond to high solar radiation (186–278 W m−2, 63–88%). Results suggest that the dimensions of holes drastically changed depending on the weather conditions and that frequent cloudy, warm and windy conditions would cause a decay of holes and weathering crust, inducing an increase in the cryoconite coverage on the ice, consequently darkening the glacier surface.